2018
DOI: 10.1080/03007995.2018.1474091
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review of health-related quality of life among aggressive non-Hodgkin lymphoma survivors

Abstract: HRQoL of NHL survivors may improve from baseline and becomes more comparable to general population HRQoL with longer survival. Overall HRQoL improvement is driven mostly by improvements in the physical domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Comparisons with other long-term survivor groups are challenging, since there are few similar populations of patients with advanced disease and durable survival. Such populations might include survivors of lymphoma, in whom findings regarding QoL are mixed, 31 and breast cancer, whose overall QoL appears comparable to controls but who may report impediments in functioning. 32 In our study, global QoL exceeded that Open access reported for the general population (median global health status 83 compared with 75 in the general population).…”
Section: Open Accessmentioning
confidence: 99%
“…Comparisons with other long-term survivor groups are challenging, since there are few similar populations of patients with advanced disease and durable survival. Such populations might include survivors of lymphoma, in whom findings regarding QoL are mixed, 31 and breast cancer, whose overall QoL appears comparable to controls but who may report impediments in functioning. 32 In our study, global QoL exceeded that Open access reported for the general population (median global health status 83 compared with 75 in the general population).…”
Section: Open Accessmentioning
confidence: 99%
“…In comparison, our review presented 82 EQ-5D-based HSUVs within the same clinical field. Other systematic reviews either aimed at HSUV identification in patients with hematologic diseases or failed to present any values (NHL survivors at least 2 years from diagnosis) 121 or else found a very limited number (2 HSUVs for AML patients not eligible for intensive chemotherapy). 122 Until now, the classic source of health utilities in this area was Pickard et al's publication from 2007, which was a systematic review of HSUVs in oncology, including 6 studies presenting 17 HSUVs for patients with leukemia, HM, NHL, or MM.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and staging of lymphoma may involve several tests including PET (positron emission tomography) scan and CT (computerised tomography) scan, and bone marrow biopsy; and lymphoma treatments can range from watchful waiting to intensive treatments including chemotherapy, radiation therapy, novel treatments and/or stem cell transplant 2 . Indeed, psychological distress is recognised as a prevalent issue among cancer patients/survivors 7 and emerging research suggests that lymphoma patients/survivors can have significantly impaired psychological wellbeing and health‐related quality of life (HRQOL) 8–13 …”
Section: Introductionmentioning
confidence: 99%
“…Existing systematic reviews have mainly synthesised studies of HRQOL in this population 8–11,17,18 . However, being one domain of a broad and multidimensional HRQOL, emotional distress is rarely discussed extensively in these reviews.…”
Section: Introductionmentioning
confidence: 99%